PERAN MANAJERIAL KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN SEKOLAH - Sabila, Nurul Hakiki; Bahtiar, Bahtiar; Yakin, Nurul (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This Research is a case study and the focus of this research is the role of the principal in improving the quality of primary school education at SDN 1 Dasan Geres, Gerung District, West Lombok Regency. This writing has the main objective, namely to determine the extent of the role of the principal in improving the quality of education, leadership, duties, and the role of the principal in improving the quality of education in elementary schools. The principal is required to understand the role that must be carried out and carried out, namely as an educator, manager, administration, supervisor, leader, innovator, or motivator. Quality education is a hope for all of us in facing challenges in various lives, especially the education sector for the future to be much better for the realization of quality education. With this, the role of the principal is needed because it is the driver of all policy directions in schools that are used to improve the quality of education in schools.